The Effect of Current Ratio, Net Profit Margin, Sales Stability, Asset Structure, and Business Risk on Capital Structure (A Study of Manufacturing Companies in the Consumer Non-Cyclical Sector Listed on the Indonesia Stock Exchange in 2019-2023) - Anaria Putri Yuliana R.M; Syafnita Syafnita; Rika Adriyana (Business, Accounting, and Knowledge Journal, 2025)
This research aims to examine the impact of current ratio, net profit margin, sales stability, asset structure, and business risk on capital structure. Capital structure is a financial decision related to optimal business funding for company operations. The study focuses object used in manufacturing company in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange (IDX) in 2019-2023 with a sample that meets the criteria of 38 so that the sampel totals 190 data. The sampling technique in this study uses purposive sampling technique. The method used in analyzing data uses Partial Least Square (PLS) – Structural Equation Modeling (SEM) and is supported by WarPLS 8.0 software. The result of the study indicate that current ratio, net profit margin, and asset structure have a negative effect on capital structure. Meanwhile, sales stability has no effect on capital structure and business risk shows a positive effect on capital structure.